Comparison of Estimated Genetic Improvement of Bali Cattle Based on The Selection of Body Dimensions - Dewi Ayu Warmadewi; I Gusti Nyoman Gde Bidura; I N Budiana (Journal of Veterinary and Animal Sciences, 2017)
Selection is one action in improving the genetic potential in animal population. Selection will be effective if the traits are varied and depends on heritability of the traits and selection intensity applied. This study was carried out using 270 breeding cows from Bali Cattle Breeding Centre in Sobangan Badung district Bali. The variables measured in this study was body length, withers height and chest girth. The results showed that the estimated selection response of body length, withers height and chest girth based on the heritability of traits and selection intensity was 0.37 cm; 0.64 cm and 1.27 cm respectively. It can be concluded that the estimated selection response of chest girth was the highest compared to body length and height of withers.